Nodular sclerosis as manifestation of monoclonal immunoglobulins deposit in multiple myeloma - Castillo-Velarde, Edwin (2019)
Monoclonal immunoglobulin deposit disease (MIDD) is a rare type of paraproteinemia that is characterized by the presence of monoclonal deposits of immunoglobulins in the basal glomerular membrane, occurring more frequently in the fifth and sixth decade of life. MIDD is subclassified in the disease by light chain deposits (LCDD), heavy chain deposit disease and light and heavy chain deposit disease, with LCDD being the most frequent form of presentation where kappa light chains are identified up to 80 % of cases, and associated to multiple myeloma in up to 50 % of patients. The finding of nodular sclerosis can be associated with LCDD in most patients.